VD_FINDINFO Décision / 2014 / 31 vom 14. Januar 2014 - VD Tribunal cantonal (2014)
DÉTENTION PRÉVENTIVE, RISQUE DE FUITE, PROPORTIONNALITÉ | 212 al. 3 CPP (CH), 221 al. 1 let. a CPP (CH), 222 CPP (CH)